Quantitative Modelling Of Corporate Efficiency And Business Growth For Unleashing Revenue Potential In Hospitality Industry - Perez, Christopher Sanchez (Digital Repository of Theses, 2025)
This dissertation investigates the relationship between corporate efficiency, business growth, and revenue potential in the hospitality industry, to develop quantitative models to assess and enhance organizational performance. The research explores insights from literature on the interplay between efficiency, growth, and revenue, identifies the determinants of corporate efficiency and their role in revenue generation, examines the key drivers of business growth and their impact on revenue potential, and develops models for measuring efficiency within hospitality operations. Adopting a quantitative, cross-sectional design, data were collected from 254 managerial and executive-level professionals using a structured questionnaire comprising 73 items across 12 thematic domains. Descriptive statistics, thematic analysis, correlation, and multiple regression were applied to identify relationships between operational practices, growth strategies, and revenue outcomes. The findings reveal that competency-based human resource practices, technology adoption, process standardization, and cost management without quality compromise are critical drivers of corporate efficiency. At the same time, customer segmentation, loyalty programs, market expansion, and superior guest experiences are central to driving business growth. The proposed quantitative efficiency models demonstrate significant predictive power for revenue performance and offer practical tools for performance benchmarking and strategic decision-making. This study contributes to theory by integrating efficiency and growth constructs into a unified quantitative framework and to practice by providing actionable insights for hospitality managers. Limitations related to sampling and self-reported data are acknowledged, with recommendations for longitudinal and mixed-method research. Overall, the research affirms that aligning efficiency with strategic growth initiatives is essential to unlocking revenue potential in the hospitality industry.